2012
DOI: 10.1161/circulationaha.111.047738
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Obesity

Abstract: Clinical summary Childhood obesity has important consequences for health and wellbeing both during childhood and also in later adult life. The rising prevalence of childhood obesity poses a major public health challenge in both developed and developing countries by increasing the burden of chronic non-communicable diseases. Despite the urgent need for effective preventative strategies, there remains disagreement over its definition due to a lack of evidence on the optimal cut-offs linking childhood BMI to dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
253
0
16

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 305 publications
(273 citation statements)
references
References 91 publications
4
253
0
16
Order By: Relevance
“…1 In the United States, obesity prevalence among children ages 6-11 years more than tripled from 4.2%-15.3% between 1963-1965 and 1999-2000. 1 Although recent studies have reported decreased obesity prevalence among younger children, in 2011-2012, 16.9% of children in the United States were classified as obese, with prevalence being highest at ages 12-19 and lowest at ages 2-5 years.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 In the United States, obesity prevalence among children ages 6-11 years more than tripled from 4.2%-15.3% between 1963-1965 and 1999-2000. 1 Although recent studies have reported decreased obesity prevalence among younger children, in 2011-2012, 16.9% of children in the United States were classified as obese, with prevalence being highest at ages 12-19 and lowest at ages 2-5 years.…”
Section: Introductionmentioning
confidence: 99%
“…1 In the United States, obesity prevalence among children ages 6-11 years more than tripled from 4.2%-15.3% between 1963-1965 and 1999-2000. 1 Although recent studies have reported decreased obesity prevalence among younger children, in 2011-2012, 16.9% of children in the United States were classified as obese, with prevalence being highest at ages 12-19 and lowest at ages 2-5 years. 2 In the past three decades, increases in obesity prevalence have been observed among children of all ages, 2,3 though differences in obesity prevalence have been documented by age, 2 race and ethnicity, 1 gender, 2 and geographic region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increases in obesity levels have been observed even in very young preschool children, which is very alarming [Lakshman et al, 2012]. A current survey in the USA has reported that among children who became obese between the ages of 5 and 14 years, nearly half had been overweight and 75% had been above the 70th percentile for body mass index at the baseline [Cunningham et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…El sobrepeso y la obesidad en adolescentes se asocian con una amplia gama de complicaciones graves para la salud y un mayor riesgo de aparición prematura de enfermedades, que incluyen diabetes mellitus tipo 2 (DM2) y enfermedades cardiovasculares 1 , las cuales constituyen las dos principales causas de mortalidad en la población general, además de otras patologías como dislipidemia, hipertensión, enfermedades musculoesqueléticas y ciertos tipos de cáncer 2,3 . De hecho, la acumulación de grasa que caracteriza el sobrepeso y la obesidad ha sido asociada con el síndrome metabólico (SM) 4 , un conjunto de elementos patológicos que comprende la obesidad abdominal, alteraciones en el metabolismo de la glucosa y los lípidos, así como una presión arterial elevada 5 .…”
Section: Introductionunclassified